A comparison between conciliation, mediation and arbitration as dispute settlement mechanisms in trade disputes in Malaysia / Noraini Nordin, Nurul Ibtisyami Yasin and Nur Adilah Abdul Ghani - Nordin, Noraini; Yasin, Nurul Ibtisyami; Abdul Ghani, Nur Adilah (2008)
A Comparison between Conciliation, Mediation and Arbitration as Dispute Settlement Mechanisms in Trade Dispute in Malaysia is a research paper focusing on alternative dispute resolution (ADR) in Malaysia, namely conciliation, arbitration and mediation. Conciliation, arbitration and mediation are topics which touch on the problems of settling trade disputes through adjudication in the Industrial Court, conciliation as in the Industrial Relations Act 1967, mediation within the Industrial Court and mediation conducted by the Malaysian Mediation Centre and arbitration under the Kuala Lumpur Regional Centre for Arbitration. This research is set out systematically, firstly dealing with the statistics on number of cases referred to the Industrial Court and factors which contribute to the high number of pending cases in the Industrial Court in Chapter Two. Secondly, Chapter Three deals with the conciliation procedures under the Industrial Relations Act 1967, parties involved in the conciliatory proceeding, roles and criteria of a conciliator, conciliation fees and advantages and disadvantages of using conciliation as a dispute settlement mechanism in trade dispute. Thirdly, Chapter Four discusses the mediation procedures, parties involved in the mediation proceeding, roles and criteria of a mediator, mediation fees and advantages and disadvantages of using mediation to settle a trade dispute. Fourthly, Chapter Five lays out the arbitration procedures under Kuala Lumpur Regional Centre for Arbitration, parties involved in the arbitral proceeding, roles and criteria of an arbitrator, arbitration fees and the advantages and disadvantages of using arbitration in settling trade dispute. Finally, Chapter Six sets out the conclusions and recommendations in settling trade disputes in Malaysia.